Configural analysis of the drinking man: Fuzzy-set qualitative comparative analyses - Eng, S.; Woodside, Arch (Pergamon, 2012)
The study here presents multiple configurations (i.e., causal recipes) of antecedents associating with heavy drinking using fuzzy-set qualitative comparative analysis (fsQCA). Using national survey data (United States), intermediate solutions of fsQCA analyses yield high consistency and modest coverage in identifying heavy-drinking groups.